The Analisis Perbandingan Terhadap Laporan Keuangan PT. Solusi Bangun Indonesia Tahun 2022 dan 2023: Analisis Perbandingan Terhadap Laporan Keuangan PT. Solusi Bangun Indonesia Tahun 2022 dan 2023 - Fortuna, Ayu Syuga; Prasetyo, Andi; Maria da Silva, Carolina (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study aims to analyze and compare the financial performance of PT Solusi Bangun Indonesia Tbk in the fiscal years 2022 and 2023 by employing financial ratio analysis. The primary focus of this research lies in examining liquidity ratios, activity ratios, debt ratios, and profitability ratios. The data utilized in this study were derived from the company's officially published annual financial statements. The analytical method applied is financial ratio analysis, which serves to assess the company’s operational efficiency and financial soundness over time. The findings reveal that, despite an increase in revenue and net income in 2023, the company’s profitability ratios experienced a slight decline due to a reduction in gross profit. Activity ratios indicate an improvement in asset utilization efficiency. Furthermore, liquidity ratios exhibited a positive trend, suggesting enhanced capability of the company to meet its short-term obligations. Concurrently, the decline in debt ratios reflects an improvement in the company's capital structure. These results provide a comprehensive insight into the company's financial performance development and may serve as a valuable reference for both managerial decision-making and investment considerations.